2009
DOI: 10.1002/cncr.24582
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cancer on spouses' labor earnings

Abstract: BACKGROUND:Cancer affects patients' incomes, but to the authors' knowledge few studies to date have examined how the income of the patients' spouses may be influenced. In this population‐based study from Norway, the effects of cancer on both partners' earnings are analyzed.METHODS:The difference between labor earnings the year before the cancer diagnosis and that 2, 5, or 8 years later was compared with the difference in earnings over a corresponding period for similar persons without cancer, applying linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
2
29
1
1
Order By: Relevance
“…Perhaps surprisingly a partner's poor health as reported by the respondent did not influence his or her work exit probability. This is in line with conclusions from an earlier review by Weaver (1994), stating that a spouse's labor supply is little affected by their partner's health, but contrary to the findings from a Norwegian register study where cancer in husband significantly lowers the work efforts of the wife (Syse et al, 2009). It is also contrasted in part by findings from Dentinger and Clarkberg (2002), suggesting that wives with husbands with care needs have up to five times higher risks for work exits, whereas the risk remains virtually unchanged for husbands with wives with care needs.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Perhaps surprisingly a partner's poor health as reported by the respondent did not influence his or her work exit probability. This is in line with conclusions from an earlier review by Weaver (1994), stating that a spouse's labor supply is little affected by their partner's health, but contrary to the findings from a Norwegian register study where cancer in husband significantly lowers the work efforts of the wife (Syse et al, 2009). It is also contrasted in part by findings from Dentinger and Clarkberg (2002), suggesting that wives with husbands with care needs have up to five times higher risks for work exits, whereas the risk remains virtually unchanged for husbands with wives with care needs.…”
Section: Discussioncontrasting
confidence: 56%
“…This has also been observed in a recent time use study from Norway (Bråthen & Bakken, 2012). However, much previous research has focused solely on female spouses' labor supply (Pozzebon & Mitchell, 1989;Siegel, 2006;Weaver, 1994) or concluded that gender differences exist so that this effect is more pronounced for women with husbands who exit the workforce compared to the other way around (Pienta, 2003;Syse et al, 2009). Surprisingly, no gender differences were observed in the effect of one spouse's work exit on that of the other in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of earnings following a cancer diagnosis can be seen in both patients and their spouses [13]. In a recent review of the impact of cancer on employment among survivors, Mehnert et al noted that only 40% of patients had returned to work 6 months after diagnosis and only two-thirds were working 5 years after diagnosis [14].…”
mentioning
confidence: 98%